Client-Server Technology, Practices of the Practical Layer - Tojiboev Ibrokhimjon Tojalievich; Mamirkhojayev Muhammadamin Mavlonjonovich; Umaraliyev Jamshidbek Tokhtasinovich; Sotvoldiyeva Mohirakhon Bakhromjon qizi; Toychibaev Abbosjon Eraliyevich (Research Parks Publishing LLC, 2022)
In this article, what is the client server, what functions does the client market; the client-server characteristic is the relationship of the interacting programs in the program. It also provides information on the client server model, networks, differences, and computing advantages.